2012
DOI: 10.1186/1471-2180-12-233
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni CsrA complements an Escherichia coli csrA mutation for the regulation of biofilm formation, motility and cellular morphology but not glycogen accumulation

Abstract: BackgroundAlthough Campylobacter jejuni is consistently ranked as one of the leading causes of bacterial diarrhea worldwide, the mechanisms by which C. jejuni causes disease and how they are regulated have yet to be clearly defined. The global regulator, CsrA, has been well characterized in several bacterial genera and is known to regulate a number of independent pathways via a post transcriptional mechanism, but remains relatively uncharacterized in the genus Campylobacter. Previously, we reported data illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…The results were similar to our observations for H. pylori J99. Interestingly, C. jejuni CsrA succeeded in recovering defects in motility, biofilm formation, and cellular morphology of csrA mutant E. coli [45]. However, similar to H. pylori CsrA, the C. jejuni CsrA ortholog was incapable of repressing glycogen accumulation in the csrA mutant E. coli [32,45].…”
Section: Discussionmentioning
confidence: 98%
“…The results were similar to our observations for H. pylori J99. Interestingly, C. jejuni CsrA succeeded in recovering defects in motility, biofilm formation, and cellular morphology of csrA mutant E. coli [45]. However, similar to H. pylori CsrA, the C. jejuni CsrA ortholog was incapable of repressing glycogen accumulation in the csrA mutant E. coli [32,45].…”
Section: Discussionmentioning
confidence: 98%
“…S2). It has been recently reported that the Campylobacter jejuni CsrA protein, expressed from an inducible araBAD promoter, does not repress glycogen production in E. coli (Fields & Thompson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This type of regulation optimizes energy expenditure and prevents the accumulation of cytosolic flagellins, which may become toxic to the bacterium. In addition, the FliW regulation of CsrA activity may provide coordinated regulation of flagellin biosynthesis and other CsrA regulated processes such as bacterial adherence, resistance to oxidative stress and virulence, although no target genes have thus far been identified (Fields and Thompson, ; Fields and Thompson, ). Theoretically, mechanisms of regulated binding of CsrA to other transcripts via additional, unidentified CsrA binding proteins may in turn affect flagellin biosynthesis by influencing the level of free CsrA.…”
Section: Discussionmentioning
confidence: 99%